Fontes e doses de nitrogênio na cultura da Brachiaria brizantha cv. xaraés sob condições edafoclimáticas de cerrado - Santini, José Mateus Kondo [UNESP] (2014)
Fertilization is undoubtedly the factor that has propitiated great response in productivity and quality of pastures. In relation to the nutrients, N deserves mention for having a great extraction and a high response of grasses in general; however, after its application, undergoes several site influences and may be lost when misused. A form that been identified as promising is the use fertilizer increased efficiency, which seek to reduce these losses. In this way, the present study aimed to evaluate sources and doses of nitrogen (N) in Xaraés grass, to enhance the efficiency of fertilizers in culture as well as contribute to increase of productivity and better nutritional values on climatic conditions of Brazilian savanna. The experiment was conducted at experimental area in the municipality of Rio Verde, GO, Brazil, with treatments distributed in a randomized blocks design with four replications in a factorial 3x4. The first factor included three sources of N (conventional urea, coated urea and ammonium nitrate); the second factor were four N doses (0, 20, 40 and 80 kg N ha-1 cutting-1). The seeding the cultivar occurred on October 10, 2012, and the first application of treatment was 50 days after emergency and collecting material 80 days after emergency, following monthly treatments. For the present work, the use of conventional urea is done as the best alternative to the culture of Brachiaria brizantha cv. Xaraés due to better cost per kg N when compared to urea coated by polymer and ammonium nitrate. The urea coated by polymer did not show greater efficiency as fertilizer. The coating used in this fertilizer did not realize its real function. The recommended dose of nitrogen is 80 kg ha-1 per cut, in view of the increased productivity of dry matter, and the maintenance of nutritional status and quality of grass bromatological Xaraés